2015
DOI: 10.1111/exd.12775
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of skin barrier function via cholinergic signal transduction in a dextran sulphate sodium‐induced colitis mouse model

Abstract: Dry skin has been clinically associated with visceral diseases, including liver disease, as well as for our previously reported small intestinal injury mouse model, which have abnormalities in skin barrier function. To clarify this disease-induced skin disruption, we used a dextran sulphate sodium (DSS)-induced colitis mouse model. Following treatment with DSS, damage to the colon and skin was monitored using histological and protein analysis methods as well as the detection of inflammatory mediators in the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 42 publications
1
29
0
Order By: Relevance
“…Previously, we separately described various biological factors associated with rheumatoid arthritis and ulcerative colitis by using a mouse rheumatoid arthritis model and a dextran sodium sulfate (DSS)-induced colitis model in mice, respectively. [6][7][8][9] In the current study, we examined DSS-induced colitis in conjunction with the rheumatoid arthritis model in mice and confirmed deterioration factors of each condition with an aim of revealing the relationship between rheumatoid arthritis and ulcerative colitis.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Previously, we separately described various biological factors associated with rheumatoid arthritis and ulcerative colitis by using a mouse rheumatoid arthritis model and a dextran sodium sulfate (DSS)-induced colitis model in mice, respectively. [6][7][8][9] In the current study, we examined DSS-induced colitis in conjunction with the rheumatoid arthritis model in mice and confirmed deterioration factors of each condition with an aim of revealing the relationship between rheumatoid arthritis and ulcerative colitis.…”
Section: Introductionmentioning
confidence: 69%
“…10) Measurement of Hind Foot Volume As a reflection of the level of edema, the hind foot volume of each mouse was measured on the final experimental day using the method described in our previous report. 6,7) Briefly, in the beaker filled with distilled water, the hind foot of each group mice was immersed to the joints, and the hind foot volume was measured.…”
Section: Experimental Animals and Collagen-induced Arthritismentioning
confidence: 99%
“…Transepidermal water loss (TEWL) and skin hydration levels in the dorsal skin were measured at 2 years after starting the experiment by using a previously described method [16]. Briefly, TEWL, a permeability measurement that reflected the barrier function of the skin, was determined using a Tewameter TM300 (Courage + Khazaka Electronic GmbH, Cologne, Germany).…”
Section: Measurement Of Transepidermal Water Loss and Skin Hydration mentioning
confidence: 99%
“…19) Additionally, it was reported that highdose vitamin C administration has anticancer effects. [20][21][22] Our previous analyses indicated that high doses of vitamin C was significantly effective against colorectal cancer (unpublished). However, the effects of high-dose vitamin C therapy on ulcerative colitis are unknown.…”
Section: Introductionmentioning
confidence: 97%